Funkcija vezničkoga spoja ako li u starohrvatskim pravnim tekstovima - Barbarić, Vuk-Tadija (2019)
U radu se analizira funkcija vezničkoga spoja ako li na korpusu koji se sastoji od odabranih starohrvatskih pravnih tekstova. Koordinate istraživanja smještaju se prema dosadašnjoj literaturi između suprotnosti i emfatičnosti, što se dalje provjerava. Pokazalo se da je Poljički statut posebno pogodan za analizu te da mnogobrojni primjeri upućuju na to da je osnovna funkcija spoja ako li da uvodi dodatni uvjet. Na kraju se upozorava na to da bi se taj spoj mogao smatrati (pojačajnim) uvjetnim konektorom.
In this paper the author analyses the complex conjunction ako li. Katičić (2002: 303) considers it a special characteristic of the old language and the vernacular that is used to introduce a clause contrasting with what has already been mentioned. A corpus consisting of Old Croatian legal texts is analysed. The choice of the complex conjunction ako li for the analysis is governed by the fact that the conjunction ako alone is a salient feature of these texts. Kuzmić (2009: 436) considers this conjunction a recognizable and important syntactic characteristic of the articles found in Old Croatian statutes. In addition, the selection of examples as well as their analysis focuses primarily on the complex conjunction ako li, as the author suspects that there is still room to define its function more clearly. Maretić (1963: 537) is also in favour of the hypothesis that the element li bears a contrasting meaning, while Pranjković (2012: 37) disagrees, considering this element an intensifier. As it is clearly shown, these hypothesis have their own prominent proponents, and are taken into account seriously in order to establish whether they hold for the period represented by the corpus. It is argued that the main function of ako li is to introduce an additional condition, and that the contrasting meaning is of no real relevance. The author proposes that this complex conjunction could be in fact considered a connector.
Bilješke uz tekst.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 274-276.
Sažetak ; Abstract.
Keywords: Starohrvatski jezik -- Pravni tekstovi -- Veznički spoj -- Intenzifikator